2018
DOI: 10.1097/phh.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Agency Accreditation Among Rural Local Health Departments: Influencers and Barriers

Abstract: The strongest predictor for seeking PHAB accreditation was serving an urban jurisdiction. Micropolitan LHDs were more likely to seek accreditation than smaller RLHDs, which are typically understaffed and underfunded. Major barriers identified by the RLHDs included fees being too high and the time and effort needed for accreditation exceeded their perceived benefits. RLHDs will need additional financial and technical support to achieve accreditation. Even with additional funds, clear messaging of the benefits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The rural percentage variable was significant and negative in the analysis, indicating that a higher percentage of rural population is associated with a lower countermeasures management score. This finding supports the literature indicating the significant public health challenges rural areas have historically faced, including funding, personnel, and other types of capacity challenges that hinder rural health departments in efforts like receiving accreditation (Beatty et al 2018). At the beginning of the pandemic, there was evidence that certain rural states were proving effective in distributing and dispensing the COVID-19 vaccines compared to their more urban counterparts (Siegler 2021).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The rural percentage variable was significant and negative in the analysis, indicating that a higher percentage of rural population is associated with a lower countermeasures management score. This finding supports the literature indicating the significant public health challenges rural areas have historically faced, including funding, personnel, and other types of capacity challenges that hinder rural health departments in efforts like receiving accreditation (Beatty et al 2018). At the beginning of the pandemic, there was evidence that certain rural states were proving effective in distributing and dispensing the COVID-19 vaccines compared to their more urban counterparts (Siegler 2021).…”
Section: Resultssupporting
confidence: 88%
“…In the study by Santibañez et al (2019), all 14 rural districts studied reported staffing as a performance challenge. Beatty et al (2018) noted that inadequate staffing presented a barrier to rural health departments receiving accreditation. Accreditation has been found to be an effective tool for generating improvement and change in public health departments, which has particular importance for rural areas (Beatty et al 2016 as cited in Beatty et al 2018).…”
Section: Rural Areas Administrative Capacity and Countermeasure Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Small jurisdiction population size and rurality are known to be associated with lower likelihood of health department accreditation or preparations for accreditation (26). Health departments with fewer employees conduct community health assessments and planning but find it difficult to address all the accreditation standards (27).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, many Healthy People goals are unmet, and only 209 LHDs had achieved accreditation as of November 20, 2018, with many indicating that the time and effort are too high for the benefit. 20 -24 In addition, no clear baseline for performance of LHDs exists. Studies investigating the performance of LHDs tend to focus on the most populous cities or health departments that opted into programs such as the National Public Health Performance Standards Program and, hence, may overestimate nationwide capacity.…”
mentioning
confidence: 99%